Changes in deoxyribonucleic acid polymerase activities in synthesis of deoxyribonucleic acid during sporulation of Bacillus subtilis. - Honjo, M (1976)
The deoxyribonucleic acid (DNA) polymerase activities in Bacillus subtilis strains Marburg 168 (thy-trp2) and D22, a DNA polymerase I-deficient mutant, were measured at various stages of sporulation. The DNA polymerase I activity, which had decreased after the exponential growth, began to increase at the early stage of sporulation, reached a maximum and then again decreased. The activity of neither DNA polymerase II nor III was observed to change so drastically as that of DNA polymerase I during sporulation. The incorporation of [3H]deoxythymidine 5'-triphosphate ([3H]dTTP) into Brij 58-treated permeable cells increased during sporulation. The stimulation of [3H]dTTP incorporation into the cells by irradiation with ultraviolet light was also observed to coincide with DNA polymerase I activity. In strain D22 the activities of DNA polymerase II and III were almost constant with time. Neither change of [3H]dTTP incorporation into Brij 58-treated cells nor stimulation of incorporation by irradiation with ultraviolet light was observed.